Large strain zero Poisson’s ratio spring cell metamaterial with critical defect analysis and variable stiffness distributions - Qin, Qing; Dayyani, Iman (Elsevier, 2023)
This paper presents novel metamaterial skins formed by 3D Spring Cells exhibiting zero Poisson’s ratio in two directions with no stress concentration on joints. Precise CAD models are generated to perform numerical and experiment analysis. High-fidelity Finite element models are developed to assess the homogenisation study of zero Poisson’s ratio. Moreover, the analytical method is also used to present for normalised Young’s modulus. Parametric study for the effect of parameter on normalised Young’s modulus and Poisson’s ratio is demonstrated based on analytical method. Pure shear analysis is demonstrated to show the off-axis loading behaviour. Structural defect analysis is investigated with regarding to its deformation mechanism under tensile strain. Furthermore, variable stiffness distribution of Spring Cell metamaterials is demonstrated while maintaining large strain zero Poisson’s ratio. The frequency and buckling analysis of metamaterials formed by spring cells are investigated and compared with equivalent shell. Moreover, their mechanical behaviours including buckling and frequency are investigated. Experiment analysis is performed to validate the force–displacement, Poisson’s ratio and deformation mechanisms discussed in numerical simulations. Finally, construction material analysis is taking to investigate the relations between metamaterial Poisson’s ratio and Young’s modulus and variety types of construction material.
Keywords: mechanical metamaterial; large strain zero Poisson’s ratio; spring structure; 3D printing; tuneable stiffness